ANALISIS KEMAMPUAN PEMECAHAN MASALAH DAN KEMAMPUAN PENALARAN MATEMATIK SISWA SMP PADA MATERI SPLDV - Santi Selvia; Tetin Rochmatin; Luvy Sylviana Zanthy (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2019)
The Purpose of this research aims to analyze the reasoning and problem solving math of the students Junior High School in the material system of equation linear two variable the descriptive and qualitative. The population of this research are the students class of  8th grade, secondary school in the district of Bandung. to obtain the data research, used instruments in the form of a description the ability and problem solving math, that each consisting of four the problem based on the analyze the value of an average all the matter of instruments, the reasoning math gained 67% and the problem solving math gained 63%. Therefore, it can be concluded that the ability to reasoning and problem solving math Junior High School students in the district of Bandung classified as enough.